CLASSPOINT APPLICATION AS A DIGITAL TRANSFORMATION IN MATHEMATICS EDUCATION - Nurus Saadah; Nonik Indrawatiningsih (Universitas Bhinneka PGRI, 2024)
The transformation to a digital platform allows the utilization of interactive tools that can create fun learning and motivate students to follow the learning process. Another tool is needed to support the learning process in understanding the material. This study aims to create learning that can motivate students through the ClassPoint application. This research is quantitative descriptive research with the research subjects of 31 first-semester students of the Informatics Engineering study program in one of the universities in East Java. The instruments used in this research are activeness set in ClassPoint, assessment results from student assignments, and response questionnaires. The data analysis technique was carried out by classifying student activeness according to the criteria, while the task results were analyzed based on the scores obtained by students. The data analysis results indicate that students are highly engaged in mathematics learning through the ClassPoint application because 74% were active and 26% were very active. It effectively helps them master mathematics materials since 90,3% of students got 80 or above as their assignment score. Students’ responses to mathematics learning are positive.